Macrophage transfer promotes intestinal mucosal healing by encouraging transit-amplifying cell expansion in mice - Kang, Dong su; Song, Young min; Park, Yeon Ji; Jeong, Hyeon Jong; Hong, Jung Joo; Seok, Seung Hyeok; Na, Yi Rang (Frontiers in Immunology, 2025)
Cellular therapy, including stem cell injections, has been proved to be therapeutic for patients with inflammatory bowel disease (IBDs), showing promising outcomes of disease progression. However, challenges of stem cell therapy remain, such as Crohn’s disease with complex fistula, thus limiting its use and requiring another cellular therapy target for efficacy. Alternatively, macrophages have been reported to enhance recovery of damaged intestinal epithelial barriers during resolution of IBDs; thus, utilizing macrophage as a therapeutic strategy was hypothesized. In this study, we compared the regenerative capacity of wild-type and Tnf− macrophages to validate the potential of genetically modified macrophages with low-inflammatory properties. Our findings demonstrate that Tnf−/− macrophage transplantation ameliorates weight loss and shortening of colon in a mouse model of colitis. Imaging mass cytometry revealed that Tnf−/− macrophages particularly increase the population of transit-amplifying cells. Cellular interaction analysis further identified a subset of fibroblast to be in proximity to these epithelial cell types. Collectively, this brief study suggests that phenotype-modified macrophage transplantation facilitates mucosal healing in IBDs, which is supporting evidence for potential cellular therapy in IBD patients.